2017
DOI: 10.1094/pdis-07-16-1055-re
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Sclerotinia Stem Rot Screening of Soybean Germplasm Requires Multiple Isolates of Sclerotinia sclerotiorum

Abstract: Sclerotinia sclerotiorum population variability directly affects Sclerotinia stem rot (SSR) resistance breeding programs. In the north-central United States, however, soybean germplasm selection has often involved only a single isolate. Forty-four S. sclerotiorum isolates from Illinois, Michigan, Minnesota, Nebraska, Wisconsin, Poland, and across 11 different host species were evaluated for variation in isolate in vitro growth, in vitro oxalate production, and in planta aggressiveness on the susceptible soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…Taylor et al (2015) demonstrated that isolates collected from diverse plant species in the UK exhibited differences in aggressiveness when inoculated onto a set of B. napus varieties. Differences in aggressiveness have also been shown on other hosts, including dandelion (Taraxacum officinale L.) (Riddle et al, 1991), sunflower (Davar et al, 2011), peanut (Arachis hypogaea L.) (Lujan et al, 2016), eggplant (Solanum melongena) (Tok et al, 2016) and soybean (Willbur et al, 2017).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Taylor et al (2015) demonstrated that isolates collected from diverse plant species in the UK exhibited differences in aggressiveness when inoculated onto a set of B. napus varieties. Differences in aggressiveness have also been shown on other hosts, including dandelion (Taraxacum officinale L.) (Riddle et al, 1991), sunflower (Davar et al, 2011), peanut (Arachis hypogaea L.) (Lujan et al, 2016), eggplant (Solanum melongena) (Tok et al, 2016) and soybean (Willbur et al, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…Differences in aggressiveness of S. sclerotiorum isolates have also been demonstrated for soybean (Glycine max (L.) Merr.) (Willbur et al, 2017). Careful considerations should therefore be made when selecting S. sclerotiorum isolates for resistance screening, since weakly aggressive isolates can increase the risk of false positive phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean plants were inoculated using the cut petiole technique ( Peltier and Grau, 2008 ) with aggressive S. sclerotiorum isolate 25 ( Willbur et al, 2017 ). A 1.5-cm-thick agar core was collected from the leading edge of mycelia on each inoculum plate with a 1,000 μl pipet tip (Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Three soybean seeds per pot were planted approximately 4 cm deep in 15.25 cm diameter peat pots of moist potting mix (Premier Pro-Mix HP BioFungicide + Mycorrhizae). Nine S. sclerotiorum isolates, of 44 previously characterized isolates with varying degrees of aggressiveness ( Willbur et al, 2017 ), were used for evaluations. As described by Willbur et al (2017) , lines were inoculated at the V4 growth stage, and lesions were measured with digital calipers (Thermo Fisher Scientific) 5, 12, and 14 DPI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation